Avaliação técnica de diferentes configurações para o tratamento de efluentes da fabricação integrada de papel Tissue e papelão - Paulino, Mariana Shiraishi (Universidade Federal de São Carlos, 2022)
Cellulose is the most abundant organic material in nature, and is a basic component of plant tissues, which provides rigidity and firmness to plants. Its uses are becoming more and more diversified in the industry, and it can currently be used to produce different types of paper (newsprint, plain white paper, cardboard), textiles, some pharmaceuticals, among others. It is common knowledge that the paper production sector is a major consumer of water. Therefore, it is of public and environmental interest that the water from the process is reused or, at least, treated to return to the environment. The growing concern with environmental preservation requires the elimination and/or reduction of the negative effects of the production process. Most of the production of jumbo rolls (which are larger, intermediate rolls that originates the final product) is quite similar in the Tissue paper and paperboard mills. The paper quality of the jumbo rolls will depend on the quality requirements in the production. Higher quality products have more pure pulp in their composition, while lower quality products have other sources of pulp materials, such as scraps. Because there is no requirement for high quality in the production of cardboard, scraps are a common component in the production of the jumbo used for this purpose. The jumbo for low quality Tissue paper production also do not require high quality control and are also produced from scraps. The use of scraps during the manufacturing process means that the effluent treatment must be more extensive and more effective than the one for the effluent from a pure pulp production. This is because the scraps are not pure raw materials, they also carry dirt and other unwanted components. Despite the similarity in the characteristics of the cellulosic raw material used in the production of tissue papers and cardboard, there are no record of integrated treatment of the effluents generated in these two types of processes. In this context, the main objective of this work was to contemplate and find the best solution for the treatment of the effluent from the production of low quality Tissue and cardboard, from the integration of the production of the types of jumbo rolls used for each one, through a technical evaluation of the different types of treatment that are available. A better result of the effluent treatment can be obtained by the combination of the Effluents Station and the anaerobic biologic treatment. Both present positive and negative point that complement each other, even though it requires a bigger initial investment.
Technical evaluation of different configurations for the treatment of effluents from the integrated manufacture of tissue paper and cardboard
Keywords: Produção de papel; Papel Tissue; Papelão; Efluentes; Tratamento; Paper production; Tissue paper; Cardboard paper; Effluents; Treatment; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA; ENGENHARIAS::ENGENHARIA QUIMICA